2021
DOI: 10.1136/neurintsurg-2021-017553
|View full text |Cite
|
Sign up to set email alerts
|

Collateral status reperfusion and outcomes after endovascular therapy: insight from the Endovascular Treatment in Ischemic Stroke (ETIS) Registry

Abstract: BackgroundStudies have suggested that collateral status modifies the effect of successful reperfusion on functional outcome after endovascular therapy (EVT). We aimed to assess the association between collateral status and EVT outcomes and to investigate whether collateral status modified the effect of successful reperfusion on EVT outcomes.MethodsWe used data from the ongoing, prospective, multicenter Endovascular Treatment in Ischemic Stroke (ETIS) Registry. Collaterals were graded according to the American … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Multiphase CT angiography (mCTA) plays an important role in the localisation of occlusion as well as in the evaluation of spatial and temporal profile of the collateral status and its patency [ 1 , 37 ]. Rapid assessment of collateral circulation downstream of occlusion is of value in the selection of candidates for EVT [ 38 ]. Whilst qualitative scoring scales of collateral assessment are commonly used, they are limited due to complex method which may be time- and skill-intensive and their broader use is limited due to the lack of a standardised method [ 1 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiphase CT angiography (mCTA) plays an important role in the localisation of occlusion as well as in the evaluation of spatial and temporal profile of the collateral status and its patency [ 1 , 37 ]. Rapid assessment of collateral circulation downstream of occlusion is of value in the selection of candidates for EVT [ 38 ]. Whilst qualitative scoring scales of collateral assessment are commonly used, they are limited due to complex method which may be time- and skill-intensive and their broader use is limited due to the lack of a standardised method [ 1 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most widely recognised grading system based on DSA is the American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology (ASITN/SIR) collateral scale [11]. Using the ASITN/SIR collateral scale, good collaterals were associated with favourable outcome in the Endovascular Stroke Treatment registry and in the Endovascular Treatment in Ischemic Stroke registry [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Collateral circulation is essential to maintain blood flow to the ischemic brain tissue in the setting of large vessel occlusions. Retrograde collaterals may additionally enhance IVT delivery to the thrombus and increase shear stress, which in turn may facilitate thrombus fragmentation by IVT 8–12. Previous studies have shown a link between robust collateral circulation and higher recanalization, thrombus shortening, and favorable functional outcome after IVT 8–11.…”
Section: Discussionmentioning
confidence: 99%
“…There is therefore an urgent need to identify factors that may help to select patients who are most likely to benefit from IVT prior to EVT with the aim to individualize therapy. Collateral circulation, which plays a major role in maintaining blood flow to the penumbral tissue, has been identified as an important predictor of successful reperfusion and favorable functional outcome after IVT and EVT 8–12. It is still unknown, however, if collateral status modifies the effect of IVT on the outcomes of EVT.…”
Section: Introductionmentioning
confidence: 99%